What has changed in the health services with the Family Health Strategy - Morais, Ildone Forte de; Oliveira, Aline Galúcio de; Azevêdo, Lorena Mara Nóbrega de; Valença, Cecília Nogueira; Sales, Linda Kátia de Oliveira; Germano, Raimunda Medeiros (Rev Rene, 2012)
This study aims to describe, through the nurses’ point of view, possible changes in health care to the population, since the implementation of the Family Health Strategy (FHS). It is an analytical study with a qualitative approach using semi-structured interviews. We interviewed six nurses from the city of Caicó-RN, who worked in primary care before and after the strategy. The major changes observed were: Ascription and links with the community, care and humanization of care, fewer hospital admissions, strengthening of disease prevention and health promotion and also improvement of health indicators. It is concluded that the FHS is a strategy that has made significant contributions to change the focus in the production of health services, with greater appreciation of the actions of disease prevention and health promotion.